The effect of salt on the physice- chemical changes occuring during the fermentation of Balao-Balao. - Lero, Marisa C. (Iloilo College of Fisheries, University of the Philippines in the Visayas, 1997)
Balao-balao is a fermented ice, shrimp and solar salt mixture in some provinces in central Luzon. It is generally prepared by mixing cooked rice, raw shrimp and solar salt and allowing the mixture to ferment for several days, no recommended procedure has been published and the manner of commercial preparations have remained in the hit-and-miss method. In this paper balaao-balao was studied for the purpose of having a better understanding of the Physico-chemical changes of this indigenous fermented product. Balao-balao with different salt concentrations i.e. 3%, 6%, 9% and 12% solar salt by weight were prepared and allowed to ferment for 21 days. Objective evaluation was conducted on the 9th day of fermentation. Objective evaluations included two chemical indices of chemical changes during the fermentation period, the amino-nitrogen and pH, which were determined daily. The solar salt content of the finished product was determined by ttitrating it with standardized silver nitrate with potassium chromate as indicator. Subjective evaluation was by sensory evaluation of odor, color, taste, texture, saltiness and general acceptability sample by 14 panelists. Fluctuations in the amino-nitrogen and pH values with fermentation period were observed, although there was in general, an increasing trend in the amino-nitrogen and a decreasing trend in pH in all levels of solar salt used in the balao-balao. Sensory evaluation was conducted only at the 3% and 6 % solar salt by weight since 9% and 12% salt by weight were observed to have a disagreeable odor on the 9th day of fermentation. Sensory evaluation and statistical analysis by t-test showed that there exist a significant difference between the balao-balao with the 3% and 6% solar salt by weight, and that the bvalao-balao with 3% solar salt was more acceptable than that with 6% solar salt.
Keywords: Feed efficiency